2021
DOI: 10.1111/gwao.12632
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking gender equity in the contaminated university: A methodology for listening for music in the ruins

Abstract: This paper offers a new way to engage with gender, race, and class relations in academic leadership and organizations. Viewing our research materials through different images helps us to ask new questions, open up new kinds of answers and ultimately other ways of knowing gender and leadership in academia. Our approach has three connected steps. Firstly, we engage with the ruins of the three main promises upon which the contemporary university has been built: enlightenment, liberalism, and feminism, drawing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…This is so even for women who, by participating in the sexist culture, receive status benefits (Alonso & O'Neill, 2022). Locke et al (2021) found that women academics who were successful in leveraging opportunities in this neoliberal masculinist landscape, do so by reproducing "existing structures and inequalities in the university" (p. 1093). Indeed, as women advance in organizations into top positions, they become less (and not more) supportive of equal opportunity programs (Ng & Chiu, 2001).…”
Section: Mckinney Et Al (mentioning
confidence: 99%
“…This is so even for women who, by participating in the sexist culture, receive status benefits (Alonso & O'Neill, 2022). Locke et al (2021) found that women academics who were successful in leveraging opportunities in this neoliberal masculinist landscape, do so by reproducing "existing structures and inequalities in the university" (p. 1093). Indeed, as women advance in organizations into top positions, they become less (and not more) supportive of equal opportunity programs (Ng & Chiu, 2001).…”
Section: Mckinney Et Al (mentioning
confidence: 99%
“…While movements exist to resist the research system and its institutions by attempting to topple them (see de Oliveira Andreotti et al, 2015), feminist modes of action work to destabilise and resist the system/institution from the inside out . For example, using the musical form of the fugue to think through the multi‐layered and textured academic lives of their participants, Locke et al (2021) discuss how their participants, women academics, ‘created a successful intersection between the ways they reshaped their discipline, used mobility to good effect, thought through their gendered relations and identities, and found moments of opportunity in university policies and structures. In some instances, they reproduced existing structures and inequalities in the university.…”
Section: Feminist Framings For Research Leadershipmentioning
confidence: 99%
“…Feminist care ethics, like affective vulnerability as part of exercising vigilance against white complicity, encourages researchers to find new, co-conspiratorial ways of relating, through collaboratively developing transformative ways of thinking about relationships and knowledge production in the first instance (Nagar, 2019;de Saxe & Ker, 2023;Locke, et al, 2021;Caputi, 2013).…”
Section: Conceptualising Reciprocitymentioning
confidence: 99%
“…It is not an easy feat to totally untether oneself from hegemonic neoliberalism in the university (Locke et al, 2021;Kidman, 2020;Connell, 2019). There is no endpoint for Pākehā settler academics working towards flipping the script in how we learn to see and understand the deep-rooted foundations which guarantee our advantage in university spaces, as well as all other parts of society (Kidman, 2020;cf.…”
Section: Conceptualising Reciprocitymentioning
confidence: 99%
See 1 more Smart Citation